Successful Social Entrepreneurship Cases in Guayaquil - Avellán-Solines, Guillermo (2018)
This paper introduces the concept of social entrepreneurship and analyzes the population benefited by the projects created by Fundación Benéfica Acción Solidaria and Humane Business School. The main purpose of the research is to demonstrate the capacity of the Social Enterpreneurship Model to become a complementary form of organization to the Popular and Solidarity Economy proposed by the former President Rafael Correa. In order to achieve this goal, the paper introduces descriptive statistics on the economic benefits and the correct selection of the favored population in these social entrepreneurship projects. This study compared the underemployed people in Guayaquil with workers associated to the Social Entrepreneurship Model. This research reveals that workers within the model receive more social benefits and earn on average a monthly income greater than informal workers in Guayaquil.